IEO Evaluation of Multilateral Surveillance : Evaluation Summary Pamphlet. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2006)
This paper presents a summary of the report by the Independent Evaluation Office (IEO) that evaluates IMF multilateral surveillance. Owing to the substantial cost to IMF of multilateral surveillance, and the key role that the IMF plays in ensuring a more stable world economy, the IEO conducted an evaluation of the IMF's multilateral surveillance activities for 2000-05. Its evaluation report commends the analytical quality of the individual components of multilateral surveillance but sees considerable scope for better coordinating these components. It also offers several suggestions for improving the effectiveness of multilateral surveillance.